2021
DOI: 10.1080/07377363.2021.1946635
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward the Inclusion of University Students with Disabilities: Barriers, Facilitators, and Recommendations Identified by Inclusive Faculty

Abstract: This study analysed the factors identified by inclusive faculty members that hinder or facilitate the inclusion of students with disabilities, and their recommendations for universities to achieve full inclusion. Forty-four inclusive faculty members participated and a biographical-narrative methodology was used. The results showed the existence of different barriers (physical, inaccessible study program, negative attitudes and inadequate educational policies). Facilitating elements were also identified (office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
1
0
2
Order By: Relevance
“…El profesorado es un sector clave de la comunidad universitaria, tanto en la ejecución de una docencia inclusiva (Llorent et al, 2020;Moriña & Orozco, 2022;Sánchez-Díaz & Morgado, 2022) como en el avance de la investigación sobre pedagogías inclusivas (Stentiford & Koutsouris, 2021). Por lo tanto, tiene sentido explorar sus creencias sobre diversidad e inclusión, ya que es probable que estas modulen la probabilidad de implementar prácticas docentes e investigadoras en el ámbito de la atención a la diversidad (Aragón et al, 2017).…”
Section: Los Significados De La Diversidad En Las Creencias Del Profe...unclassified
“…El profesorado es un sector clave de la comunidad universitaria, tanto en la ejecución de una docencia inclusiva (Llorent et al, 2020;Moriña & Orozco, 2022;Sánchez-Díaz & Morgado, 2022) como en el avance de la investigación sobre pedagogías inclusivas (Stentiford & Koutsouris, 2021). Por lo tanto, tiene sentido explorar sus creencias sobre diversidad e inclusión, ya que es probable que estas modulen la probabilidad de implementar prácticas docentes e investigadoras en el ámbito de la atención a la diversidad (Aragón et al, 2017).…”
Section: Los Significados De La Diversidad En Las Creencias Del Profe...unclassified
“…No obstante, muchos estudios ponen de manifiesto que, en ocasiones, los docentes universitarios no logran facilitar el aprendizaje y la participación de sus estudiantes, especialmente aquellos con algún tipo de discapacidad (Fernández-Gámez et al, 2021; Louise & Swartz, 2022). No es de extrañar, pues, que se haya identificado al profesorado como una pieza clave para alcanzar una educación universitaria inclusiva (Li et al, 2021; Llorent et al, 2020; Melero et al, 2020; Sánchez-Díaz & Morgado, 2021).…”
Section: Estrategias De Aprendizaje Inclusivo En La Universidad: La P...unclassified
“…However, many studies have concluded that faculty members sometimes fail to facilitate the learning and participation of their students, especially those with disabilities (Fernández-Gámez et al, 2021; Louise & Swartz, 2022). It is not surprising, therefore, that faculty members have been identified as a key player in achieving inclusion (Li et al, 2021; Llorent et al, 2020; Melero et al, 2020; Sánchez-Díaz & Morgado, 2021).…”
mentioning
confidence: 99%